DIGITIZATION OF AUDIT ACTIVITY: PROBLEMS AND DEVELOPMENT PROSPECTS - Антышева, Елена; Полищук, Виктория (SWorldJournal, 2021)
The active digital transformation of the economy affects all areas of activity, and the field of audit is no exception. The large amounts of data generated by digital technologies make the work of auditors much more difficult. Accordingly, with the digit